(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article examines the issue of the influence and relationship between the teacher’s pedagogical culture and the formation of health-saving competence of future specialists. The question of the importance of this problem was considered, which consists in the following: the successful work of enterprises and educational institutions depends on the quality of training of specialists, and the state of physical health of specialists is also important. Pedagogical culture is understood as a component of universal human culture that combines historical and cultural pedagogical experience and regulates the sphere of pedagogical interaction. Pedagogical culture is a field of practical activity that includes the accumulated experience of a teacher, which is aimed at improving educational processes, which also involve the development of relationships and the following of cultural values. It has been proven that the connection between the teacher and the student is best carried out in a certain environment created by the teacher, in particular, in a health-preserving environment. The health-preserving environment is defined as a component of the educational environment, which develops through the implementation of health-preserving educational technologies. In such an environment, the health care competence of a specialist is formed. Health-preserving competence is understood as an integral quality of a person, which is manifested in their general ability to health-preserving activities and is based on the integration of knowledge, abilities, skills, value orientations of the individual to preserve physical, social, mental and spiritual health. It was determined that a teacher can ensure the formation of health-preserving competence of future specialists, since the structure of their pedagogical culture includes the following components: pedagogical knowledge; pedagogical feelings and motives; pedagogical beliefs; organizational and pedagogical abilities; communication culture; pedagogical tact; physical education; culture of health. The process is carried out in a health-preserving environment.